Modelica/CD++ : a tool for continuous systems modeling based on the DEVS formalism - D'Abreu, Mariana (2004)
The DEVS formalism is a method defined for modeling and simulation of discrete event systems.During the last years the DEVS theory has evolved, and it was recently upgraded in order to permit simulation of continuous and hybrid systems. In this work, we present a tool for modeling and simulation of continuous systems based on the DEVS formalism. Models are described using Modelica, a modular and acausal standard specification language for physical systems modeling. Examples of model simulation with their execution results are included. The results are compared against those given by a commercial tool, implementing the simulation of physical systems using the classical integration methods based on the discretization of time.